The white working class : what everyone needs to know - Gest, Justin (What everyone needs to know., 2018)
Who are white working class people? What do they believe? What has driven them to break so sharply with the world's trajectory toward a more borderless, interconnected meritocracy? The White Working Class: What Everyone Needs to Know® presents the context for understanding the political ideologies, actions, and behavior of this complicated constituency. Providing an accessible introduction to the white working class, this book argues that they must be understood if the world is to address and respond to the social and political phenomena they are driving.